(untitled) (Journal of Global Accounting, 2025)
The study examined the determinants of environmental disclosures in the Nigeria oil and gas sector. Secondary data was retrieved from the corporate annual reports of the sampled companies. Descriptive statistics, ordinary lease square analysis, endogeneity test, fixed and random effect estimation, Hausman tests were all carried out. Regression tests such as normality, multi-collinearity, Heteroskedasticity and serial correlation tests were also carried out. The study revealed that profitability improves environmental disclosure. Meanwhile, leverage reduces environmental disclosure significantly. However, company size does not affect environmental disclosure significantly. The study concludes profitability and leverage are major drivers of environmental disclosure significantly. Hence, firms are advised to pay more attention to environmental reporting, firms irrespective of their leverage level should improve their environmental performance; both small and big firms should improve their environmental performance.